IbM di POSYANDU RW 4 DAN RW 5 DESA TAMBAKSARI - Rini, Susilo; Sugiharti, Rosi Kurnia (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2017)
This article describes the results of IbM activities in Posyandu RW 4 and RW 5 of Tambaksari Village which have high maternal and infant morbidity and mortality problems during childbirth and low exclusive breastfeeding (ASI) coverage. This activity is aimed to form the support group of childbirth (KP-Nifas) in 2 posyandu that is posyandu RW 4 and RW 5 of Tambaksari Village which is expected to optimize the role of K cadre in empowering the puerperal mother and her family, so that mother and baby through the puerly period with healthy and fun . Stages of activities undertaken in the establishment of the KP Nifas are among others: 1) Licensing, 2) Coordination, 3) Establishment of Childbirting KP, 4) Creation of Materials 5) Cadre training, and 6) Posyandu implementation with KP Nifas.Â The Output target of the science and technology results for the society (IbM) is to be a scientific paper published in scientific journals, its formed KP Nifas, the availability of KP nifas booklet, postpartum care leaflets, newborn care and exclusive breastfeeding management and videos that help Increase public awareness and knowledge about the importance of care and support for postpartum and exclusive breastfeeding. The attendance of this postpartum Support Group can facilitate access to information in two posyandu held every month by the community to consult the sharing of experiences and information between postpartum women, cadre and health personnel so as to minimize problems during the puerperium and increase exclusive breastfeeding coverage.Keywords: Supporting Group of Postpartum Mother, Posyandu